Risk factors and incidence rate of complications originated as a consequence of the acute SARS-CoV-2 infection or the treatments performed. A longitudinal study in general medicine from March 15, 2020 to October 31, 2022 in Toledo, Spain - Jose Luis Turabian (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
Background: The epidemiological data on complications originated as a consequence of the acute infection of COVID-19 or the treatments performed are not well known. Objectives: To estimate the incidence rate and the risk factors of complications originating as a consequence of the acute infection of COVID-19 or the treatments performed in general practitioner consultation. Methodology: A prospective study of patients with COVID-19 in a general practice setting in Toledo, Spain, from March 15, 2020, to October 31, 2022. Results: 687 positive cases of acute COVID-19 were diagnosed. Of these, 36 (36% were women and 39% had >=65 years old) presented complications, which represents a gross incidence rate of 5%. In >=65 years old, the incidence rate was 23%. The incidence rate of complications was much higher in 2020 vs. 2021 and 2022 (21%, 5%, and 1% cases, respectively). The only statistically significant risk factors were aged > = 65 years (RR = 2.46), having presented moderate-severe severity of primary infection (RR = 14.54) having chronic diseases (RR = 3.11), and specifically of the circulatory system (RR = 1.98). Conclusion: In the context of general medicine in Toledo (Spain) incidence rate of complications originated as a consequence of acute infection of COVID-19 or the treatments performed, was higher in cases with acute infection in 2020, and in >=65 years old, and are risk factors having presented moderate-severe severity of primary infection, having chronic diseases, and specifically of circulatory system, and being >= 65 years old.